2007
DOI: 10.2310/7290.2007.00025
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and Cellular Trafficking of Magnetic Nanoparticles for Prostate Cancer Imaging

Abstract: Antibody-conjugated iron oxide nanoparticles offer a specific and sensitive tool to enhance magnetic resonance (MR) images of both local and metastatic cancer. Prostate-specific membrane antigen (PSMA) is predominantly expressed on the neovasculature of solid tumors and on the surface of prostate cells, with enhanced expression following androgen deprivation therapy. Biotinylated anti-PSMA antibody was conjugated to streptavidin-labeled iron oxide nanoparticles and used in MR imaging and confocal laser scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 20 publications
(23 reference statements)
3
48
0
Order By: Relevance
“…9 Labeled with the appropriate antibodies to tumor membrane antigens, nanoparticles offer great specificity and sensitivity. 10 One potential candidate, overexpressed in both local and metastatic prostate cancer, is prostate stem cell antigen. 11,12 In contrast with other prostate cancer-associated tumor antigens, prostate stem cell antigen has been recognized as a truly prostate-specific membranebound protein, which participates in membrane recycling and becomes internalized by ligand-induced endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…9 Labeled with the appropriate antibodies to tumor membrane antigens, nanoparticles offer great specificity and sensitivity. 10 One potential candidate, overexpressed in both local and metastatic prostate cancer, is prostate stem cell antigen. 11,12 In contrast with other prostate cancer-associated tumor antigens, prostate stem cell antigen has been recognized as a truly prostate-specific membranebound protein, which participates in membrane recycling and becomes internalized by ligand-induced endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…These probes were based on potential capitalization on PSMA as a relevant biologic target for imaging and therapy of prostate cancer. Other works indicated that biotinylated anti-PSMA antibody conjugated to streptavidin-labeled iron oxide nanoparticles could be used as the MRI probe for detection of prostate cancer cells [37]. T1-weighted signal was greater for cells with magnetic particles bound to cell surface than for cells that internalized the particles, whereas no such effect was noted with T2-weighted images.…”
Section: Imaging Probes For Prostate Cancer Based On Psmamentioning
confidence: 99%
“…The difference was statistically significant (P<0.0001). High resolution confocal imaging suggested that internalized nanoparticles localized to the late endosomal/lysosomal compartment, as would be expected following receptor-mediated uptake (Serada et al 2007). In addition, the nanoparticles co-localized with viral nanoparticles that have been previously demonstrated to localize to the late endosomal compartment (data not shown) (Lewis et al 2006).…”
Section: Binding and Internalization Assaysmentioning
confidence: 99%
“…However, there are only a few recent examples of MRI contrast agents targeted specifically to prostate cancer cells. Antibodies (Serada et al 2007) and aptamers (Wang et al 2008) targeting the prostate-specific membrane antigen expressed on prostate cancer cells have been conjugated to SPIO, facilitating selective binding and uptake. Selective imaging of prostate cancer cells in vivo was also recently achieved by the conjugation of SPIO to peptides targeting hepsin, a prostate cancer biomarker (Kelly et al 2008).…”
Section: Introductionmentioning
confidence: 99%